2001
DOI: 10.1021/tx000222a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Reaction Scheme Describing Malondialdehyde−Acetaldehyde−Protein Adduct Formation

Abstract: Malondialdehyde and acetaldehyde react together with proteins and form hybrid protein conjugates designated as MAA adducts, which have been detected in livers of ethanol-fed animals. Our previous studies have shown that MAA adducts are comprised of two distinct products. One adduct is composed of two molecules of malondialdehyde and one molecule of acetaldehyde and was identified as the 4-methyl-1,4-dihydropyridine-3,5-dicarbaldehyde derivative of an amino group (MDHDC adduct). The other adduct is a 1:1 adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…We have shown that MDA and acetaldehyde can react with collagen to give a potential cross-linking dihydropyridine product (3), and others (6,7) have confirmed this finding. However, under the same conditions, 70 mM MDA hardly cross-links 25 mg/ml bovine serum albumin (BSA) (8), 2 as demonstrated by the absence of an observable dimer band on SDS-PAGE gels after this time period.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…We have shown that MDA and acetaldehyde can react with collagen to give a potential cross-linking dihydropyridine product (3), and others (6,7) have confirmed this finding. However, under the same conditions, 70 mM MDA hardly cross-links 25 mg/ml bovine serum albumin (BSA) (8), 2 as demonstrated by the absence of an observable dimer band on SDS-PAGE gels after this time period.…”
supporting
confidence: 71%
“…Only a potentially unlikely second reaction with MDA opens the possibility of cross-linking again, probably via a dihydropyridine-type structure reported previously (3,6,8). A variety of synthetic experiments are being carried out to investigate the potential reaction mechanism proposed in Scheme 2.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To address the former possibility, the SP-A-mediated aggregation of auto-oxidized liposomes containing increased concentrations of lipid hydroperoxides was compared with that of nonoxidized liposomes, and no differences were found. LPO also leads to the formation of reactive aldehydes that have been shown to derivatize proteins (47,48). The addition of MDA at two to four times higher concentrations than levels reached during LPO under the conditions used had no effect on lipid aggregation rate or end point.…”
Section: Discussionmentioning
confidence: 97%
“…A 3,4,5-trisubstituted 1,4-dihydropyridine structure is formed, closely resembling that of the antihypertensive Ca-channel blocker drug nifedipine (Scheme 9) (Tuma et al, 2001). It is totally speculative to wonder whether such metabolites may be physiologically occurring and may play a role in blood pressure regulation.…”
Section: Mass Spectrometry and Protein Adductsmentioning
confidence: 99%